2000 Revisited - Visionen der Welt von morgen im Gestern und Heute - Rothenhausler, Andie; Dobroć, Paulina (Karlsruher Studien Technik und Kultur, 2020)
Visions of the future have a performative effect as they trigger political debates and articulate societal grievances, hopes and fears. Time horizons envisaged in them - such as the year 2000 - often become synonymous with the future itself. This volume brings together case studies from history, philosophy, sociology, and technology assessment in order to show the effectiveness of future visions and the significance of socio-technical deadlines.